2018
DOI: 10.1186/s12906-018-2129-5
|View full text |Cite
|
Sign up to set email alerts
|

Traditional healing practices in rural Bangladesh: a qualitative investigation

Abstract: BackgroundTraditional healing practice is an important and integral part of healthcare systems in almost all countries of the world. Very few studies have addressed the holistic scenario of traditional healing practices in Bangladesh, although these serve around 80% of the ailing people. This study explored distinctive forms of traditional healing practices in rural Bangladesh.MethodsDuring July to October 2007, the study team conducted 64 unstructured interviews, and 18 key informant interviews with tradition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
62
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 18 publications
8
62
0
1
Order By: Relevance
“…A snowball technique was used to identify the 24 IDI participants (6 from each cluster) that helped reach those that were considered difficult to access [19]. As mentioned, this study selected influential urban participants and was carried out with a diverse range of both tobacco users and non-users in terms of age, ethnicity, religion, education and economic status.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A snowball technique was used to identify the 24 IDI participants (6 from each cluster) that helped reach those that were considered difficult to access [19]. As mentioned, this study selected influential urban participants and was carried out with a diverse range of both tobacco users and non-users in terms of age, ethnicity, religion, education and economic status.…”
Section: Methodsmentioning
confidence: 99%
“…Similar concepts that emerged from thematic analysis were identified and drawn together to from common themes and sub-themes. [19]. In this way, although the IDIs were analyzed separately, inferences were drawn collectively from the results.…”
Section: Methodsmentioning
confidence: 99%
“…It highly prevents women to seek maternal care from medical practitioners. In addition, a strong belief in witchcraft or the evil eye on pregnant women is a major component of many cultures [50][51][52][53]. In order to ward off evil spirits and the in uence of supernatural powers on pregnant women, the elderly of the family, most likely a mother-in-law, take the decision to consult spiritual healers [54,55].…”
Section: Discussionmentioning
confidence: 99%
“… 12 Further to that, studies from different settings have shown that traditional healing is perceived to have positive impacts such as social and spiritual well-being, meaningfulness of life 13 and symptom improvement. 14 However, the contextually-specific knowledge of why traditional healing is perceived to be effective and why different people use different sectors of healthcare for mental health complaints remains understudied. This knowledge however remains pivotal as it could provide a bridge to strengthen the pathways which populations naturally use for their health complaints; and be used to empower local populations in the process of improving mental health interventions.…”
Section: Introductionmentioning
confidence: 99%